CTP Synthase 2 From Arabidopsis thaliana Is Required for Complete Embryo Development - Hickl, Daniel; Scheuring, David; Möhlmann, Torsten (Frontiers in Plant Science, 2021)
Pyrimidine de novo synthesis is an essential pathway in all organisms. The final and rate limiting step in the synthesis of the nucleotide CTP is catalyzed by CTP-Synthase (CTPS) and Arabidopsis harbors five isoforms. Single mutant lines defective in each one of the four isoforms do not show apparent phenotypical alterations in comparison to wild-type plants. However, Arabidopsis lines which contain T-DNA insertions in the CTPS2 gene were unable to produce homozygous offspring. Here we show that CTPS2 exhibits a distinct expression pattern throughout embryo development and loss of function mutants are embryo lethal, as siliques from +/ctps2 plants contained nearly 25 % aborted seeds. This phenotype was rescued by complementation with CTPS2 under control of its endogenous promoter. CTPS2::GFP lines revealed expression only in the tip of columella cells in embryo root tips of the heart and later stages. Furthermore, CTPS2 expression in mature roots, most pronounced in the columella cells, shoots and vasculature tissue of young seedlings was observed. Filial generations of +/ctps2 plants did not germinate properly, even under external cytidine supply. During embryo development the CTPS2 expression pattern resembled the established auxin reporter DR5::GFP. Indeed, the cloned promoter region we used in this study possesses a repeat of an auxin response element and auxin supply increased CTPS2 expression in a cell-type specific manner. Thus, we conclude that CTPS2 is essential for CTP supply in developing embryos and loss of function mutants in CTPS2 are embryo lethal.